Diastolic function assessed from tagged MRI predicts heart failure and atrial fibrillation over an 8-year follow-up period: the multi-ethnic study of atherosclerosis. (20th October 2013) - Ambale-Venkatesh, Bharath; Armstrong, Anderson C.; Liu, Chia-Ying; Donekal, Sirisha; Yoneyama, Kihei; Wu, Colin O.; Gomes, Antoinette S.; Hundley, Gregory W.; Bluemke, David A.; Lima, Joao A.
Abstract: Objectives: The strain relaxation index (SRI), a novel diastolic functional parameter derived from tagged magnetic resonance imaging (MRI), is used to assess myocardial deformation during left ventricular relaxation. We investigated whether diastolic function indexed by SRI predicts heart failure (HF) and atrial fibrillation (AF) over an 8-year follow-up. Methods: As a part of the multi-ethnic study of atherosclerosis, 1544 participants free of known cardiovascular disease (CVD) underwent tagged MRI in 2000–02. Harmonic phase analysis was used to compute circumferential strain. Standard parameters, early diastolic strain rate (EDSR) and the peak torsion recoil rate were calculated. An SRI was calculated as difference between post-systolic and systolic times of the strain peaks, divided by the EDSR peak. It was normalized by the total interval of relaxation. Over an 8-year follow-up period, we defined AF ( n = 57) or HF ( n = 36) as combined ( n = 80) end-points. Cox regression assessed the ability of SRI to predict events adjusted for risk factors and markers of subclinical disease. Integrated discrimination index (IDI) and net reclassification index (NRI) of SRI, compared with conventional indices, were also assessed. Results: The hazard ratio for SRI remained significant for the combined HF and AF end-points as well as for HF alone after adjustment. For the combined end-point, IDI was 1.5% ( P < 0.05) and NRI was 11.4% ( P < 0.05) for SRI. Finally, SRI was more robust than all other existing cardiovascular magnetic resonance diastolic functional parameters. Conclusion: SRI predicts HF and AF over an 8-year follow-up period in a large population free of known CVD, independent of established risk factors and markers of subclinical CVD.